Synergistic Approach to Diastema Closure using Frenectomy and Restorative Procedures: A Case Report - Varshini Raman; Deepak Moses Ravindran; Divya Kumar; Lekha Ashokumar; SK Balaji (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Midline diastema, the space between maxillary central incisors, is a common aesthetic concern with multifactorial aetiology. A 24-year-old female presented with a midline diastema caused by a high papillary frenum, contributing to multifactorial aesthetic disharmony. This created aesthetic concerns and anterior asymmetry. Digital diagnostics, including intraoral scanning and virtual smile design, supported accurate assessment and planning. Treatment involved a diode laser frenectomy to remove the high frenal attachment and restore gingival zenith harmony. This was followed by diastema closure using a digitally guided injectable resin composite technique. A 3D-printed mock-up and customised injection template helped achieve precise morphology, controlled resin placement, and strong aesthetic results while preserving tooth structure. Postoperative review at three months showed smooth healing, high patient satisfaction, and stable functional and aesthetic outcomes with no relapse. This case highlights the combined benefits of laser-assisted surgery and digitally guided restorative methods. The approach offers a minimally invasive, predictable, and refined solution for treating diastema linked to high frenal attachment.